A practical synthesis of optically active δ-nitro-α-ketoesters and 4-cyclohexyl-proline catalyzed by chiral squamides. Issue 24 (31st December 2015) - Liu, Ri-long; Yan, Yun-yun; Zhang, Ting; Zhang, Xue-jing; Yan, Ming
Graphical abstract: Abstract: Inexpensive and readily available squamides derived from 9-amino-9-deoxyepiquinine or 9-amino-9-deoxyepiquinidine were found to be superior catalysts for the asymmetric conjugate additions of t -butyl nitroacetate to β, γ-unsaturated-α-ketoesters. After the subsequent decarboxylation with silica gel, a variety of δ-nitro-α-ketoesters were obtained in good yields and with excellent enantioselectivities. The products were further transformed into ethyl 4-aryl-prolinate via a cascade nitro reduction and amination. A new synthesis of (2 S, 4 S )-4-cyclohexyl-proline was also developed. A practical synthesis of optically active δ-nitro-α-ketoesters and 4-aryl-proline derivatives is described. Abstract : (2 R, 4 S )-Ethyl 5-nitro-4-phenyl-2-(tosyloxy)pentanoate: C20 H23 NO7 S [ α ]D 20  = +24.0 ( c 0.7, CH2 Cl2 ) Absolute configuration: (2 R, 4 S ) Abstract : (2 S, 4 S )-4-Cyclohexylpyrrolidine-2-carboxylic acid: C11 H19 NO2 [ α ]D 20  = −31.8 ( c 0.2, AcOH) Absolute configuration: (2 S, 4 S )